2009
DOI: 10.1016/j.chemphys.2009.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic properties of ethyl 5-(4-dimethylaminophenyl)-3-amino-2,4-dicyanobenzoate

Abstract: Dedicated to Professor Józef Heldt on the occasion of his 75th birthday Keywords:Ethyl 5-(4-dimethylaminophenyl)-3-amino-2,4-dicyanobenzoate Charge transfer fluorescence Donor-acceptor system a b s t r a c tWe report the synthesis and photophysical properties of ethyl 5-(4-dimethylaminophenyl)-3-amino-2,4-dicyanobenzoate (EDMAADCy) in neat solvents of different polarity. The relation between molecular conformations of molecule under study and spectral behavior has been studied using steady-state spectroscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…We found that for EAADCy molecule the ground-state rotational potential is essentially flat (in the range from 60° to 120°) [18, 19]. Figure 1a shows the calculated ground-state ( S 0 ) rotational potential and the corresponding rotamer distribution function n ( φ ) determined from Boltzmann’s low at 298 K, for the molecule under study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that for EAADCy molecule the ground-state rotational potential is essentially flat (in the range from 60° to 120°) [18, 19]. Figure 1a shows the calculated ground-state ( S 0 ) rotational potential and the corresponding rotamer distribution function n ( φ ) determined from Boltzmann’s low at 298 K, for the molecule under study.…”
Section: Resultsmentioning
confidence: 99%
“…To test whether the changes in the absorption, fluorescence excitation and fluorescence spectra originate from the solute conformers possesing different angles between their interatomic planes of the donor and acceptor moieties, a series of conformational semiempirical quantum mechanical calculations were carried out. We found that for EAADCy molecule the ground-state rotational potential is essentially flat (in the range from 60° to 120°) [ 18 , 19 ]. Figure 1a shows the calculated ground-state ( S 0 ) rotational potential and the corresponding rotamer distribution function n ( φ ) determined from Boltzmann’s low at 298 K, for the molecule under study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As it was mentioned, we have recently undertaken spectroscopic studies of the ICT properties of EAADCy. It has been shown in our previous papers that the photophysical properties of EAADCy are very sensitive to the microenvironment. On the basis of the experimental results and quantum-chemical calculations, it has been shown that the fluorescence spectra of EAADCy in medium polar solvents consist of two bands at room temperature. The short-wavelength (SW) band corresponds to the emission from the locally excited state (mainly emission of the excited acceptor moiety).…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the results of our previous publications, this study focuses on the improved and complete knowledge of the charge transfer process in EAADCy. In order to clarify the excited-state dynamics of EAADCy, which would greatly facilitate its application in NLO material studies, we have carried out a series of femtosecond transient absorption and time-resolved nanosecond fluorescence measurements of the title compound in solvents of varying polarity and viscosity.…”
Section: Introductionmentioning
confidence: 99%